Empreendedorismo internacional: a capacidade de inovar no grupo de empresas paraibanas de tecnologia digital - Freitas, Monalisa Tatiane de Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
With digital transformation leveraging the competitiveness of the business environment, the need arises for organizations to conquer international markets. In this internationalization process, there are several aspects involved that need to be explored, among them is the ability to innovate. In order to develop a study related to this dimension, this research aims to analyze how the ability to innovate affects the international entrepreneurship of a group of digital technology companies located in João Pessoa/PB. For this, a qualitative research was developed that had as data collection method the semi-structured interviews and as data analysis method the content analysis of Bardin (2011). From the data collected, we can identify aspects of the ability to innovate that help the internationalization process, such as the ability to internationalize, the technical and personal capabilities of managers, the evolution of products and markets, the flexibility to recognize opportunities, resource management, technology, and the competitive advantage of organizations. Analyzing the incidence of these aspects, it was evidenced the expressive participation of the leaders in the innovation and internationalization process, and the similarities and divergences of the ability to innovate among the three companies investigated
Keywords: Empreendedorismo internacional; Internacionalização; Tecnologia; Inovação; Capacidade de inovar; Pesquisa qualitativa; Atlas.ti; International entrepreneurship; Internationalization; Technology; Innovation; Ability to innovate; Qualitative research; Atlas, ti; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES